Essential ski characteristics for cross-country skis performance - Bäckström, M.; Dahlen, L.; Tinnsten, M. (The Engineering of sport 7, Volume 2, 2008)
Winner or trail hog? Much depends on the ski characteristics. The manufacturing of skis is a complicated process involving several materials and different process steps. This gives as a result that every ski obtains unique characteristics such as span curve and bending stiffness etc. For high performance skiers as the member of the Swedish ski team the importance of equal characteristics of each ski in a pair is vital. The process of matching skis to a pair is the process of finding two individual skis with the most similar characteristics. This is traditionally done by hand with simpler equipment. Our measurement system is developed for faster and more accurate ski characteristics assessment. The characteristics do impose the overall performance of the ski. It produces the span curve with very high accuracy and gives a good representation of the pressure distribution over the full length of the ski. The measured characteristics could, in our opinion, also be used in selecting skis for different weather and track conditions. The ski measurement system has been used by the Swedish cross-country team during the last 2,5 years which have resulted in a faster and more accurate matching of skis. In collaboration with the Swedish ski team have also an investigation concerning correlation between ski characteristics and weather and track conditions has been initiated with some preliminary results already obtained.